Cicatricial alopecia. (12th April 2018) - Kanti, Varvara; Röwert‐Huber, Joachim; Vogt, Annika; Blume‐Peytavi, Ulrike
Summary: In the classification of the North American Hair Research Society, primary cicatricial alopecias (PCA) are divided into four groups according to their prominent inflammatory infiltrate: PCAs with lymphocytic, neutrophilic, mixed or nonspecific cell inflammation pattern. The hair loss can begin subclinically and progress slowly so that the exact onset of the disease is often difficult to determine. The diagnosis is often delayed. While most forms of cicatricial alopecia can be clearly diagnosed based on clinical presentation in the acute disease stage, diagnosis can be challenging in the subacute, early or late disease stages. At first presentation, a detailed patient history and dermatological examination of the body, including trichoscopy, should be performed. In clinically unclear cases, a biopsy should be performed. Due to the scarcity of primary cicatricial alopecia, there is little evidence on the efficacy of the various therapies. The aims of treatment are to stop or at least delay hair loss and progression of the scarring process, reduce clinical inflammation signs as well as to alleviate subjective symptoms. Hair re‐growth in already scarred areas should not be expected. Anti‐inflammatory treatment with topical corticosteroids class III to IV and / or with intracutaneous intralesional triamcinolone acetonide injections can be considered in most of the primary cicatricial alopecias. The choice of systemic therapy depends on the type of predominant inflammatory infiltrate and includes antimicrobial, antibiotic or immunomodulating/immunosuppressive agents. Psychological support and camouflage techniques should be offered to the patients.